Shopping day and time preferences of Malaysian hypermarket consumers - Hassan, Hasliza; Rahman, Muhammad Sabbir; Abu Bakar Sade, Sade (Australian Academy of Business and Social Sciences Pty Ltd. ACN 167 587 377, 2015)
This research looks at consumer preference concerning shopping day and time within the Malaysian market. There are five main hypermarket players in Malaysia. The analysis of this research is based on cross-tabulation analysis between the hypermarket players and the preferred shopping day and time. Data were collected from hypermarket consumers throughout Malaysia based on proportionate convenience sampling survey technique. The findings from this research indicate that the majority of the respondents do not have any specific preferred day or time to shop. However, a consistently high percentage of the respondents prefer to shop at the weekend and late evening. It is also found that there is a significant association between the hypermarket players and the preferred shopping day and time. Since there is no study on hypermarket consumers within the Malaysian market, this research is a breakthrough discovery for the consumer preference concerning shopping day and time.